1996
DOI: 10.1093/cercor/6.5.661
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric Anatomical Differences in Human Primary Auditory Cortex: Probabilistic Mapping and Volume Measurement from Magnetic Resonance Scans

Abstract: The gyral morphology of the region of the primary auditory cortex (PAC) in the human brain is highly variable, and possible asymmetries between the hemispheres have been noted since the beginning of the century. We mapped the location and extent of PAC as identified from gross anatomical landmarks in magnetic resonance scans that had been transformed into Talairach-Tournoux stereotaxic space. Individual maps were averaged to produce a probabilistic map of the region which can be co-registered with any image of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

46
393
5
8

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 546 publications
(452 citation statements)
references
References 31 publications
46
393
5
8
Order By: Relevance
“…By contrasting signal strength of illusory speech-like sounds (illusion) with acoustically very similar nonspeech sounds (illusion break) in the core (primary) auditory cortex and speech areas (speech ROI), we can perhaps identify functionally distinguishable regions in the auditory cortex. To do this, we first estimated the coordinates of HG by averaging across four separate estimates of the center of either HG (Patterson, Uppenkamp, Johnsrude, & Griffiths, 2002;Penhune, Zatorre, MacDonald, & Evans, 1996) or cytoarchitectonically defined the PAC Rademacher et al, 2001). All four sets of coordinates are published in Patterson et al (2002, Table 1).…”
Section: Perception Of Illusorily Continuous Vowelsmentioning
confidence: 99%
“…By contrasting signal strength of illusory speech-like sounds (illusion) with acoustically very similar nonspeech sounds (illusion break) in the core (primary) auditory cortex and speech areas (speech ROI), we can perhaps identify functionally distinguishable regions in the auditory cortex. To do this, we first estimated the coordinates of HG by averaging across four separate estimates of the center of either HG (Patterson, Uppenkamp, Johnsrude, & Griffiths, 2002;Penhune, Zatorre, MacDonald, & Evans, 1996) or cytoarchitectonically defined the PAC Rademacher et al, 2001). All four sets of coordinates are published in Patterson et al (2002, Table 1).…”
Section: Perception Of Illusorily Continuous Vowelsmentioning
confidence: 99%
“…28 The primary auditory cortex is located approximately in half of the first gyrus or in half of the first gyrus and in part of the second gyrus; it covers about the central two thirds of Heschl's gyrus. 25,[28][29][30] Many studies have demonstrated the existing asymmetry between the right and left Heschl's gyruses. The left gyrus is larger than the right gyrus; thus, the left primary auditory cortex is also larger than the right primary auditory cortex.…”
Section: Introductionmentioning
confidence: 99%
“…The increased left size volume results from more gray and white matter present in this side. 28,31,32 The larger neural substrate (more neurons and more intra-and interhemispheric interconnections) in these left hemisphere anatomic structures provides the basis for better language development compared to the corresponding (smaller) areas in the right side. 32 Left hemisphere speech specialization may be related to an identification of specific acoustic parameters for sound and speech discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, many groups have noted the importance of probabilistic atlases and have made probability maps using different modalities and different methodologies. Probability maps for subregions of normal brains have been reported (Amunts et al, 1999(Amunts et al, , 2000Kennedy et al, 1998;Leonard et al, 1998;Loftus et al, 1995;Paus et al, 1996;Penhune et al, 1996;Rademacher et al, 2001aRademacher et al, ,b, 2002Thompson et al, 1996a;Tomaiuolo et al, 1999;Varnavas and Grand, 1999;Westbury et al, 1999;White et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Probability maps of planum temporale and primary auditory cortex, using MRI parcellations (Penhune et al, 1996), and primary auditory cortex, using cytoarchitectonic parcellations (Rademacher et al, 2001b), have been published for normal control subjects. However, little is known of the anatomical and distributional abnormalities in these areas and, to our knowledge, no probability maps have been created based on manually delineated ROIs in first-episode schizophrenia.…”
Section: Introductionmentioning
confidence: 99%